Evaluation of The 1office-Integrated System Using an Adaptation to The Delone and Mclean Success Model - Bayu Dewantoro; Irman Hermadi; Joko Ratono (School of Business, IPB University (SB-IPB), 2019)
This study aimed to evaluate the successful implementation of 1Office integration system at PT Grundfos Indonesia by an adaptation to DeLone and McLean model. The 1Office is a system that should be applied in all Grundfos's companies, according to the instructions from its headquarter. There are 6 variables to evaluate in the DeLone and McLean model, namely Service Quality, System Quality, Information Quality, Use, User Satisfaction and Net Benefits. Using a quantitative approach, questionnaires were used as a technique for data collection. The data obtained then was analyzed using SEM PLS (Structural Equation Modeling Partial Least Square) and purposive sampling on 60 users. The results showed that Service Quality has a positive effect on Use and User Satisfaction, so does System Quality on User Satisfaction. Furthermore, User Satisfaction has a positive influence on Net Benefits as the effectiveness of using information systems, which has an impact on user groups, organisations, suppliers, and customers at PT. Grundfos Indonesia.Keywords: 1Office system, DeLone and McLean model, PT Grundfos Indonesia, SEM PLS